Increase in precipitation and fractional vegetation cover promote synergy of ecosystem services in China’s arid regions—Northern sand-stabilization belt - Wei, Changwen; Su, Kai; Jiang, Xuebing; You, Yongfa; Zhou, Xiangbei; Yu, Zhu; Chen, Zhongchao; Liao, Zhihong; Zhang, Yiming; Wang, Luying (Frontiers in Ecology and Evolution, 2023)
Research on synergies and trade-offs between ecosystem services (ES) contributes to a better understanding of the linkages between ecosystem functions. Relevant research mainly focuses on mountain areas, while research in arid areas is obviously insufficient. In this study, we took the northern sand-stabilization belt (NSB) as a case study. Based on five simulated ecosystem services (habitat provision, sand-stabilization service, water conservation service, soil conservation service and carbon sequestration service), the Pearson correlation coefficient method was used to analyze the various characteristics of the trade-offs and synergies among the different ES pairs along the fractional vegetation cover (FVC) and precipitation gradients. Results showed that: The trade-offs and synergies among multiple ES were widespread in NSB, but synergies account for a greater proportion. Changes in FVC and precipitation gradients could strongly enhance and weaken the trade-offs and synergies of some paired ES. Synergies between most paired ES increased significantly with increasing precipitation and FVC. However, ES have different sensitivities to environmental change, precipitation promotes more synergy of ES pairs than FVC. The study also found that land use/land cover may be an important driving factor for trade-offs and synergies between paired ES. This study can improve our understanding of arid and semi-arid (or macro-regional) ecosystems and contribute to the development of ecosystem management and conservation measures in the NSB.